2018
DOI: 10.1109/tpwrs.2017.2727075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Optimal Storage Allocation on Price Volatility in Energy-Only Electricity Markets

Abstract: Abstract-Recent studies show that the fast growing expansion of wind power generation may lead to extremely high levels of price volatility in wholesale electricity markets. Storage technologies, regardless of their specific forms e.g. pump-storage hydro, large-scale or distributed batteries, are capable of alleviating the extreme price volatility levels due to their energy usage time shifting, fast-ramping and price arbitrage capabilities. In this paper, we propose a stochastic bi-level optimization model to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The impact of optimal allocation of both strategically and non-strategically behaving ESS on price volatility in energy-only markets was investigated by Masoumzadeh et al [124]. They showed that, although an ESS is able to decrease price volatility, it does not remove it completely, and the positive impact stops when the ESS reaches the profitability limit.…”
Section: Strategic Ess Investmentsmentioning
confidence: 99%
“…The impact of optimal allocation of both strategically and non-strategically behaving ESS on price volatility in energy-only markets was investigated by Masoumzadeh et al [124]. They showed that, although an ESS is able to decrease price volatility, it does not remove it completely, and the positive impact stops when the ESS reaches the profitability limit.…”
Section: Strategic Ess Investmentsmentioning
confidence: 99%
“…In recent years, many scholars have carried out a series of fruitful work to alleviate the wind curtailment problem, such as energy storage optimization configuration (Dicorato et al, 2012;Del Rosso and Eckroad, 2014;Zheng et al, 2015b;Lu et al, 2018;Masoumzadeh et al, 2018;Al Ahmad and Sirjani, 2020;Padhee et al, 2020), and joint planning of energy storage and transmission grids (Zheng et al, 2015a;Qiu et al, 2017;Bustos et al, 2018;Dvorkin et al, 2018;Jorgenson et al, 2018;Yacar et al, 2018;Zhang and Conejo, 2018;Nikoobakht and Aghaei, 2019;Sima et al, 2019;Wu and Jiang, 2019). In terms of energy storage optimization configuration, Padhee et al, (2020) proposed a hybrid energy storage optimization configuration method for the intermittency and uncertainty of renewable energy, while Al Ahmad and Sirjani (2020) combined the discretization method, multi-objective hybrid particle swarm algorithm and nondominated sorting genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The fluctuation of renewable energy output brings about the problem of fluctuations in electricity prices. Masoumzadeh et al, (2018) using energy storage makes the electricity market price fluctuate at a certain level. Energy storage configuration can not only increase the flexibility of the system (Lu et al, 2018), but also delay the construction of transmission lines (Del Rosso and Eckroad, 2014), so the joint planning of energy storage and transmission grids has attracted extensive research interest.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, [9] focuses on analyzing the consumer reaction and their willingness to shift demand under demand response programs. In contrast, the optimal size of energy storage as a demand-side flexibility resource for addressing price volatility in a renewable generation-dominant electricity market is investigated in [10].…”
Section: Introductionmentioning
confidence: 99%